PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH, MUSYARAKAH DAN ISTISHNA’ TERHADAP TINGKAT PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Andriani Andriani; Maida Sari (Indonesian Journal of Applied Accounting and Finance, 2021)
The aim of the research is to determine the effect of murabaha, mudharaba, musyarakah and istishna financing on the level of profitability (ROA) of Islamic Banks(IB) in Indonesia. The result shows that score of R2 less then 50% which implied that the model of the research is not sufficient in explaining the ROA level in IBs. It is aligned with the previous study that used similar dependent and independent variables. Murabaha, mudharaba, musyarakah and istishna financing simultanuously and significantly affect the level of profitability in IBs. Mudharaba financing significantly and positively affects the level of profitability while musyaraka financing significantly and negatively affects the level of profitability of IBs. In contrary, istishna and murabaha financing does not significantly affects the level of profitability.